Harnessing Complexity for Better Outcomes in Public and Non-profit Services - French, Max (Policy Press, 2023)
ePDF and ePUB available Open Access under CC-BY-NC-ND licence. Building on research in public health, social epidemiology and the social determinants of health, this book presents complexity theory as an alternative basis for an outcome-oriented public management praxis. It takes a critical approach towards New Public Management and provides new conceptual inroads for reappraising public management in theory and practice.